SERAPAN LEMBAGA KEUANGAN MIKRO SYARIAH DI SUMATERA BARAT TERHADAP LULUSAN PROGRAM STUDI D.III MANAJEMEN PERBANKAN SYARIAH - TESTRU HENDRA; IRSADUNAS IRSADUNAS (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
The purpose of the study was to determine the absorption of Islamic Microﬁnance Institutions in West Sumatra towards graduates of the study program D.III Islamic Banking Management UIN Imam Bonjol Padang. This type of research is qualitative research, namely research that aims to produce descriptive data about oral and written words, and behavior that can be observed from the people studied. The results of the study are: 1) The percentage of graduates absorbed by Islamic microﬁnance institutions in West Sumatra is still very small, which is 4.3% of the total number of graduates from 2008-2017 totaling 738 people. 2) The percentage of graduates working at Islamic microﬁnance institutions in West Sumatra is already good, if seen from the number of tertiary institutions in West Sumatra, which is 11% of the total number of employees of Islamic microﬁnance institutions in Sumatra in 2008-2017 totaling 262 person.